Under the table : Using video(de)creation to imagine gestures of political Child - Menning, Soern Finn (Reconceptualizing Educational Research Methodology, 2024)
Centred around a one-minute short film of an everyday activity in a Norwegian early childhood education institution, this article will explore how thinking with video offers the ability to deconstruct and re-imagine taken-for-granted conceptions of children’s political participation. Sensitive to aesthetic dimensions of video, this research-creation emphasises bodily intensities and collective vitality often less noticed in childhood research. Paired with both a close and an in-depth reading of Manning´s (2016) minor gestures as political as well as Agamben’s (1992, 1995) conception of gesture, the use of the cinematic technique of montage enables us to challenge dominant methodological discourses in the investigation of children’s agency. While the major gestures of political child are often based on identifying children’s individualised subject-centred and discourse-based agency, this multi-modal article will explore how video as research-creation might contribute to reconceptualising political child differently.